2010
DOI: 10.1021/bm1002398
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin/Montmorillonite Nanocomposites: Effect of pH on the Conformational Transition and Clay Dispersion

Abstract: By adjusting the solution pH value below the isoelectric point (pI) of silk fibroin (SF) protein, the SF was in the cation state and it could interact strongly with unmodified anionic montmorillonite (MMT) surface. In this way, novel SF-MMT nanocomposites with good clay dispersion were successfully obtained, which were confirmed by X-ray diffraction and transmission electron microscopy. Further 1H CRAMPS and 13C CP/MAS NMR experimental results revealed that beta-sheet content of SF was remarkably enhanced for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 60 publications
(110 reference statements)
2
68
1
Order By: Relevance
“…This lack of one single preferential motif in L is consistent with the flat pattern obtained from our XRD analysis (Fig. 5), and might agree with the random coil conformation proposed in previous studies [69].…”
Section: Study By Cp-mas "C Nmrsupporting
confidence: 93%
See 4 more Smart Citations
“…This lack of one single preferential motif in L is consistent with the flat pattern obtained from our XRD analysis (Fig. 5), and might agree with the random coil conformation proposed in previous studies [69].…”
Section: Study By Cp-mas "C Nmrsupporting
confidence: 93%
“…In fact, although the signals attributed by Dang et al to a psheet conformation [69] matched those observed in Silk II by Asakura and Yao [65], the chemical shift identified by the latter author with an ordered repeated pll-turn in Silk I [64,65] was associated by Dang and coworkers with a random-coiled distribution of the fibroin molecules [69]. In the study on the conformational transition from Silk I to Silk II, Zhou and colleagues describe the former state as 'helix dominant' [46].…”
Section: Study By Cp-mas "C Nmrmentioning
confidence: 90%
See 3 more Smart Citations